Theory of Planned Behavior: Aplikasi pada Konsumen Rumah Sakit - Handayani, Siti Dyah (Jurnal Manajemen Bisnis, 2011)
The theory of planned behavior proposed by Ajzen states that the factors which influence a person in choosing or not choosing a product include attitude toward behavior, subjective norm, and perceived behavioral control. The main purpose of this research is to apply the theory of planned behavior on the hospitals consumers. It would, first, identify attitude toward behavior of the consumers of hospitals; second, identify the subjective norm and referent which are mostly influential; third, identify the influence of attitude toward behavior, subjective norm, and perceived behavioral control toward the behavioral intention simultaneously and partially; and fourth, identify the variables that are mostly influential on behavioral intention of hospital service.The subjects of the research were consumers of PKU Muhammadiyah Hospital of Yogyakarta. The sampling technique employed was purposive convenience sampling, which involved 100 respondents (respondense rate = 83.33%). The results showed that the attitude toward behavior of the hospital consumers is in the category of medium with the attitude score percentage of 54.8375%. The highest attitude toward behavior  score is on the doctors services and the lowest score is on the service rate. Subjective norm is in the category of medium, with the score percentage of 50.666%. The most influential referent is family. These three variables, that is attitude toward behavior, subjective norm and perceived behavioral control positively influence the behavioral intention, either simultaneously or partially. Subjective norm becomes the most influential variables for the behavioral intention on hospital services.